2015
DOI: 10.4172/2155-6156.1000615
|View full text |Cite
|
Sign up to set email alerts
|

Angiotensin-(1-7): A Novel Peptide to Treat Hypertension and Nephropathy in Diabetes?

Abstract: The renin-angiotensin system (RAS) plays a pivotal role in mammalian homeostasis physiology. The RAS can be delineated into a classical RAS (the pressor arm) including angiotensinogen (Agt), renin, angiotensin-converting enzyme (ACE), angiotensin II (Ang II) and angiotensin type 1 receptor (AT1R), and a counterbalancing novel RAS (the depressor arm) including Agt, renin, angiotensin-converting enzyme-2 (ACE-2), angiotensin-(1-7) (Ang 1-7) and Ang 1-7 receptor (or Mas receptor (MasR)). Hyperglycemia (diabetes) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(17 citation statements)
references
References 51 publications
0
17
0
Order By: Relevance
“…Recently, numerous scientific researchers have proved the extensive physiological and pathophysiological properties of Ang-(1-7) on the progress of diabetes. Previous findings have shown that Ang-(1-7) functions in reducing systematic hypertension, oxidation, fibrosis and inflammation 21 . However today, the beneficial effects of Ang-(1-7), as a protection opposition to HG-stimulated injuries, are still unclear.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, numerous scientific researchers have proved the extensive physiological and pathophysiological properties of Ang-(1-7) on the progress of diabetes. Previous findings have shown that Ang-(1-7) functions in reducing systematic hypertension, oxidation, fibrosis and inflammation 21 . However today, the beneficial effects of Ang-(1-7), as a protection opposition to HG-stimulated injuries, are still unclear.…”
Section: Introductionmentioning
confidence: 99%
“…However, RAAS activation during ACE inhibition or angiotensin-receptor blockade may favor the renoprotective effects of the RAAS cascade, including angiotensin 1–7 (Ang-1–7) production and the activation of type-2-angiotensin-II receptor (AT 2 R) and Mas receptors (MasR) [69]. In contrast to the pressor arm of the RAAS (angiotensin-II–AT 1 R axis), a significant body of evidence has shown that the depressor arm (Ang-1–7–MasR) axis exerts beneficial effects against DN [70]. Ang-1–7, which is produced from angiotensin-II by ACE2, is a heptapeptide found in the heart and kidneys and a specific ligand for MasR that has anti-inflammatory, antioxidative stress, and vasodilatory effects [71].…”
Section: Mechanisms Underlying the Renoprotection Exerted By Sglt2mentioning
confidence: 99%
“…[46][47][48] In addition, through the Mas receptor, angiotensin-(1-7) has been shown to reduce signalling pathways thought to be responsible to fibrogenesis and chronic inflammation. 49 Animal studies have shown an additive benefit of SGLT2i to angiotensin-converting enzyme inhibitors (ACEi) in slowing the progression of diabetic nephropathy 50 and lowering BP, [51][52][53] an effect that might be linked to upregulation of the non-classical pathway.…”
Section: Mechanisms Of Kidney Protectionmentioning
confidence: 99%